Railway Safety Education via Interactive Gamification Learning - Mat Kashim, Mohd Amir Rashdan; Misnan, Mohd Saidin; Jenuwa, Norsyazwana; Ab. Wahid, Abdul Muhaimin; Ab Malek, Siti Nor Faizah (UiTM Cawangan Perlis, 2024)
Gamification in education uses gaming mechanics to make traditional learning environments more engaging and interactive. This approach enhances student engagement and promotes active participation by incorporating rewards, competition, achievements, and progress tracking. Hazard hunts are instrumental in pre-emptively managing workplace safety by ensuring hazards are promptly recognized, assessed, and mitigated. The Safety Railway Game provides high levels of enjoyment and engagement compared to traditional teaching methods, with mean agreement and importance ratings for having fun and enjoying the lesson/game session being both 4.9 out of 5. Studies provide further support for using gamification to enhance learning sessions and increase student enjoyment.